JENIS-JENIS BURUNG DI PERKEBUNAN KELAPA SAWIT PONDOK PESANTREN HASANATUL BAROKAH ROKAN HULU - Saputra, Reski; Purnama, Arief Anthonius; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about bird species at Hasanatul Barokah palm oil plantation was conducted on December 2014. With Survey methods has been used in this research. The research station technique by purposive random sampling. The researcher found that 10 family 12 species and 27 individual, that Alcedinidae (Halcyon smyrnensis), Ardeidae (Ixobrychus cinnamomeus), Columbidae (Geopelia striata, Spilopeliachinensis, Treron vernans), Meropidae (Merops viridis), Muscicapidae (Copsychus saularis), Phasianidae (Coturnix chinensis), Psittacidae (Psittacula longicauda), Pycnonotidae (Pycnonotus aurigaster, Pycnonotus simplex), Sturnidae (Acridotheres cinereus). Index diversity is category medium, with value 2,185.